INTEGRASI ANALISIS KESESUAIAN LOKASI TPS3R DAN PERSEPSI MASYARAKAT DALAM MENDUKUNG PENGELOLAAN SAMPAH BERKELANJUTAN DI KOTA DENPASAR (Jurnal Arsitektur ARCADE, 2026)
Waste management has become one of the major urban environmental challenges in Denpasar City due to increasing waste generation and limited waste treatment capacity. The closure of Suwung Landfill has further emphasized the importance of strengthening communitybased waste management facilities such as TPS3R (Reduce, Reuse, Recycle Waste Processing Sites). This study aims to analyze the suitability of TPS3R locations with the Detailed Spatial Plan (RDTR), identify community perceptions toward TPS3R, and examine the relationship between spatial suitability and community perception. This research employed a quantitative descriptive approach using questionnaires, field observations, and document analysis. Thirteen TPS3R locations in Denpasar were evaluated against the RDTR, while community perceptions were analyzed using Likert-scale questionnaires. Data were analyzed descriptively and using Spearman Rank Correlation. The results indicate that most TPS3R locations are spatially compatible with the RDTR, community perceptions tend to be positive, and there is a significant relationship between location suitability and community perception. The findings provide recommendations for sustainable spatial planning and community-based waste management in Denpasar.